2017
DOI: 10.1590/1980-57642016dn11-010011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cognitive training program and sleep hygiene for executive functions and sleep quality in healthy elderly

Abstract: IntroductionThe aging process causes changes in the sleep-wake cycle and cognition, especially executive functions. Interventions are required to minimize the impact of the losses caused by the aging process.ObjectiveTo evaluate the effects of a cognitive training program and psychoeducation on sleep hygiene techniques for executive functions and sleep quality in healthy elderly.MethodsThe participants were 41 healthy elderly randomized into four groups ([CG] control group, cognitive training group [CTG], slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
0
9
0
2
Order By: Relevance
“…It is important to note that adequacy of the sleep environment is part of the recommendations regarding sleep hygiene, which comprises behavioral and environmental practices which aim to promote good sleep quality and adequate duration. 55 In addition, students who daily commute to the university probably had to wake up earlier, since it took more than 1 hour to get to the university, which led to a decrease in their sleep duration during school days in relation to other students. This longer travel time to the institution was associated with waking up earlier and a significant reduction in sleep duration in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that adequacy of the sleep environment is part of the recommendations regarding sleep hygiene, which comprises behavioral and environmental practices which aim to promote good sleep quality and adequate duration. 55 In addition, students who daily commute to the university probably had to wake up earlier, since it took more than 1 hour to get to the university, which led to a decrease in their sleep duration during school days in relation to other students. This longer travel time to the institution was associated with waking up earlier and a significant reduction in sleep duration in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they obtained gains in sleep quality and a reduction in terms of excessive daytime sleepiness. Thus, they concluded that cognitive training and sleep interventions were successful strategies for improving cognitive performance, as well as for the quality of sleep in the older adults ( 56 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated positive health outcomes as a result of participation in cognitive training interventions, including enhanced cognitive performance and functional ability (Ball et al, 2002; Borella et al, 2010; Brehmer et al, 2012; Cantarella et al, 2017; Kelly et al, 2014; Rebok et al, 2014; Willis et al, 2006), lowered depressive symptoms (Motter et al, 2016; Wolinsky et al, 2009), improved sleep (Almondes et al, 2017; Diamond et al, 2015; Keramtinejad et al, 2019), and overall increases in general health and well-being (Wolinsky et al, 2006). Cognitive training may impact mortality risk through its beneficial effects on cognitive, functional, and physical and mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%